Dye-sensitized solar cells with hole-stabilizing surfaces: "inorganic" versus "organic" strategies1. Issue 47 (27th May 2015) - Hostettler, Nik; Wright, Iain A.; Bozic-Weber, Biljana; Constable, Edwin. C.; Housecroft, Catherine E.
<x xml:space="preserve">Abstract</x> A study of organic and zinc(ii)-containing DSC sensitizers with second-generation diphenylamino-dendrons and benzothiadiazole domains shows that the organic dye has a superior performance.